Adolescents' Attitudes about Teenage Marriage - Faiza Khalifatunnisa Lukmansyah; Restuning Widiasih; Deni Kurniadi Sunjaya; Binahayati Rusyidi; Laili Rahayuwati; Ermiati Ermiati (Universitas Jember, 2024)
Adolescence is a period of crisis where if one phase in the period is not well passed, it will push adolescents into problems, one of which is teenage marriage. However, studies related to adolescents' attitudes towards marriage in adolescence for areas that are at high risk of experiencing an increase in marriage in adolescence are still limited. This research aims to obtain an overview of teenagers' attitudes in the Bangka Belitung Islands Province regarding early marriage in terms of 7 related dimensions. This research is a documentation study of secondary data from the research team